Hubungan Peran Teman Sebaya dan Status Kesehatan dengan Manajemen Perawatan Diri pada Lansia: The Relationship of Peer Roles and Health Status to the Management of Self-Care in the Elderly - Oselita, Ostalia (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Self-care management in the elderly is judged by their ability to perform daily activities. Daily life activities are functions and activities that are normally done without the help of others. The purpose of this study is to determine the relationship between peer roles and health status in the management of self-care in the elderly at Panti Werda Budi Thersna Mulya South Jakarta in 2017. Methods: This study uses a cross-sectional design. The sample is 117 elderlies as respondents research. Results: The results showed that most of the peer roles, health status, and management of self-care in Panti Werda Budi Thersna Mulya South Jakarta are good. There is a relationship between peer role in the management of self-care in the elderly with a value of P = 0.026. There is a correlation between health status and management of self-care in the elderly with a P-value = 0.035. Discussion: Research suggestion expected after knowing the results of this study, elderly can further improve the management of self-care in their old age to avoid the feeling of loneliness facing old age.